Substance and Essence in Aristotle : An Interpretation of "Metaphysics" VII-IX - Witt, Charlotte, 1951- (Book collections on Project MUSE., 1989)
Substance and Essence in Aristotle is a close study of Aristotle's most profound-and perplexing-treatise: Books VII-IX of the Metaphysics. These central books, which focus on the nature of substance, have gained a deserved reputation for their difficulty, inconclusiveness, and internal inconsistency. Despite these problems, Witt extracts from Aristotle's text a coherent and provocative view about sensible substance by focusing on Aristotle's account of form or essence. After exploring the context in which Aristotle's discussion of sensible substance takes place, Witt turns to his analysis of essence. Arguing against the received interpretation, according to which essences are classificatory, Witt maintains that a substance's essence is what causes it to exist. In addition, Substance and Essence in Aristotle challenges the orthodox view that Aristotelian essences are species-essences, defending instead the controversial position that they are individual essences. Finally, Witt compares Aristotelian essentialism to contemporary essentialist theories, focusing in particular on Kripke's work. She concludes that fundamental differences between Aristotelian and contemporary essentialist theories highlight important features of Aristotle's theory and the philosophical problems and milieu that engendered it.